UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI MEDIA PERMAINAN KARTU BERGAMBAR PADA SISWA KELAS 1 MI NW SEKUNYIT - Sukawati, Sukawati (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
This study aims to describe how the use of picture card games (flashcards) in grade 1 students of MI NW Sekunyit for the 2021/2022 academic year and to improve reading skills in the beginning of Indonesian in class I MI students. This research is a Classroom Action Research (CAR) carried out in 2 cycles with 3 meetings in each cycle with a total of 31 students. In the pre-action the percentage of new students' completeness reached 23%, after the action was carried out in cycle I the percentage of students' completeness increased to 55%, in cycle II it increased to 77% so the researcher did not proceed to cycle III.